Familia Parapaguridae (Anomura, Paguroidea) en Chile: Nuevos registros de cangrejos ermitaños de profundidad - Nicole Olguín (Revista de Biología Marina y Oceanografía, 2014)
Two new distribution records of hermit crabs of the family Parapaguridae, i.e., Oncopagurus haigae and Sympagurus dimorphus are presented. The material examined was collected by 2 expeditions from the Chilean coast. The PUCK-156 and INSPIRE Expeditions in 2001 and 2010, respectively, at depths ranging from 340 to 1300 m. The present study provides taxonomic and distributional information as well as a key to aid in the identification of the species of Parapaguridae present in waters off Chile. With these results the family in southe ast Pacific waters off Chile is represented by 14 species belonging to the genera Oncopagurus (3 species), Paragiopagurus (3 species), Parapagurus (3 species), Sympaguru s (3 species), Strobopagurus (one species) and Tylaspis (one species).